The Authority On Endorsement Of Marriage Agreement Between Indonesian And Foreign Citizen Which Made Abroad - Fitri Khairunnisa (Unram Law Review, 2018)
Every citizen is entitled to marry with anyone either with fellow Indonesian Citizens or with Foreign Citizens (WNA), as long as the marriage is held in accordance with the provisions of applicable law in Indonesia. The method of this research using a normative legal method which are conducted the file through library conduct and regulation, by find the meaning and requirement to do the prenuptial agreement. a prenuptial agreement is an agreement between two person to arrange their personal property made before, during or after marriage, and authorized by the marriage registry officer. The marriage agreement, which was then made abroad, then created a problematic one for who was authorized to legalize the marriage agreement to then have legal force in Indonesia.